Clinical translation of theranostic radiopharmaceuticals: Current regulatory status and recent examples - Kolenc Peitl, Petra (J Labelled Comp Radiopharm, 2019)
With the development of ever more radiopharmaceuticals suitable for theranostic applications, translation of novel compounds from the preclinical stage towards clinical application becomes a bottleneck for the advances in Nuclear Medicine. This review article summarizes the current regulatory framework for clinical trials with radiopharmaceuticals in the European Union, provides a general overview of the documentation required, and addresses quality, safety, and clinical aspects to be considered. By using a recent successful example of translating a theranostic peptide radioligand, namely (111)In‐CP04, which targets receptors expressed in medullary thyroid carcinoma, the pathway from the preclinical development over establishing the required pharmaceutical documentation to designing and submitting a clinical trial is reviewed. Details regarding preclinical data, generation of the documentation, and final successful application are described. This article should provide an insight in an ever more complex process to bring innovations in the field of radiopharmaceuticals into patients.